2020
DOI: 10.1002/agj2.20061
|View full text |Cite
|
Sign up to set email alerts
|

Limited irrigation influence on rotation yield, water use, and wheat traits

Abstract: Selecting more water‐efficient wheat (Triticum aestivum L.) varieties that are suited to no seasonal irrigation is an important way to improve water use efficiency (WUE) in the North China Plain (NCP). The goal of this study was to assess the yield and WUE of wheat, maize (Zea mays L.), and rotation, and to determine the traits of high‐WUE wheat varieties and clarify the mechanism for increasing WUE. Experiments were conducted during the 2012–2016 seasons using 10 common winter wheat varieties under no seasona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 61 publications
2
4
0
Order By: Relevance
“…Rainfall could effectively supplement the demands for crop water demands and supply the soil water stock, particularly in the winter wheat season. Even though, the water that the winter wheat season required was still up to 200-300 mm (Fang et al, 2010;Sun et al, 2010), and irrigation could be contributed to crop yield production, e.g., the yield of S086 for W0 vs. W1 vs. W2 was 6536 vs. 8182 vs. 8286 kg ha -1 , in 2019-2020 (Table 5), which indicated that irrigation could increase crop yields by as high as 27-164%, and these results have been proved by previous studies (He et al, 2017;Zhang et al, 2020). The selection of drought-resistant varieties was also bene cial for irrigation water saving with high crop yield.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Rainfall could effectively supplement the demands for crop water demands and supply the soil water stock, particularly in the winter wheat season. Even though, the water that the winter wheat season required was still up to 200-300 mm (Fang et al, 2010;Sun et al, 2010), and irrigation could be contributed to crop yield production, e.g., the yield of S086 for W0 vs. W1 vs. W2 was 6536 vs. 8182 vs. 8286 kg ha -1 , in 2019-2020 (Table 5), which indicated that irrigation could increase crop yields by as high as 27-164%, and these results have been proved by previous studies (He et al, 2017;Zhang et al, 2020). The selection of drought-resistant varieties was also bene cial for irrigation water saving with high crop yield.…”
Section: Discussionsupporting
confidence: 68%
“…However, SWC primarily differed in the 0-120 cm soil layer in these different irrigation treatments (Fig. 2) Zhang et al, 2020). In addition, the extraction of deeper soil water was increased when the irrigation water was reduced (i.e., W0 and W1) (Xu et al, 2016).…”
Section: In Uence Of Irrigation On Soil Water-holding Consumptionmentioning
confidence: 96%
See 1 more Smart Citation
“…Intensified winter wheat planting is the primary cropping system in northern China, which produces >67% of the wheat in China [1]. Northern China is a typical semi-arid area with an average annual precipitation of 556 mm, but only 27-32% (150-180 mm) of this falls during the winter wheat growing season [2]. Consequently, precipitation cannot meet the requirements, and a lack of adequate water thus causes up to a 200-300 mm shortage of water during the whole winter wheat growing season [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Ningxia had favorable environmental conditions: high temperature in crop growing season, large day and night temperature difference, sufficient solar radiation with sufficient irrigation and good management practices made large improvements of yield possible (Yang, 2017). For Hebei, the cultivation of drought-tolerant varieties and crops with low water consumption alleviated the restriction of drought on yield (Zhang et al, 2020). The yield increased in Shaanxi province due to modern dry-land cultivars (Sun et al, 2014) and increasing solar radiation (Chen et al, 2017).…”
Section: Spatial and Temporal Variation Of Yieldmentioning
confidence: 99%